Analysis of Patient Satisfaction on the Quality of Physiotherapy Services in the Pandemic Era at the SHC - Rifaidwianto Ngguna; Erlina Puspitaloka Mahadewi; Gisely Vionalita; Rini Handayani (CV. Inara, 2022)
The present study about Satisfaction is the perception of a product or service that has metexpectations. The customer satisfaction is the result of the accumulation of consumers or customers in using products or services. The quality of health services is the degree to which the needs of the community or individuals are meet for healthcare in accordance with good professional standardswith the use of resources fairly, efficiently, effectively within the limited capacity of the government and the community, and is carried out safely and satisfies customers in accordance with accepted good norms and ethics. Based on observations made by distributing customer feedback questionnaires at the Sasana Husada Clinic (SHC), Jakarta Indonesia patient satisfaction in outpatient physiotherapy services from January to March 2021. Result for patient satisfactionobtained 76%, of which there were about 24% who were dissatisfied with the physiotherapy servicesprovided at the SHC Jakarta Indonesia. The purpose of this study was to determine the analysis of patientsatisfaction with the quality of physiotherapy services in the covid-19 pandemic era at the SHC. Thestudy used a descriptive observational method with a cross sectional research design. The sample in this study was 62 people with sampling technique using simple random sampling. This research was conducted by filling out a questionnaire by the patient. Data analysis was performed by univariate test analysis. The results of the study indicate that patient satisfaction inside pandemic and based on thequality dimension of reliability 79.61%, patient satisfaction based on the assurance dimension 80.06%, patient satisfaction based on the tangibility quality dimension 81.67%, patient satisfaction based on the empathy quality dimension 78.12%, satisfaction patients based on responsiveness 77.80% and general patient satisfaction 78.06%.